Monitoring Poly(ADP-ribosyl)glycohydrolase Activity with a Continuous Fluorescent Substrate. Issue 12 (20th December 2018) - Drown, Bryon S.; Shirai, Tomohiro; Rack, Johannes Gregor Matthias; Ahel, Ivan; Hergenrother, Paul J.
Summary: The post-translational modification (PTM) and signaling molecule poly(ADP-ribose) (PAR) has an impact on diverse biological processes. This PTM is regulated by a series of ADP-ribosyl glycohydrolases (PARG enzymes) that cleave polymers and/or liberate monomers from their protein targets. Existing methods for monitoring these hydrolases rely on detection of the natural substrate, PAR, commonly achieved via radioisotopic labeling. Here we disclose a general substrate for monitoring PARG activity, TFMU-ADPr, which directly reports on total PAR hydrolase activity via release of a fluorophore; this substrate has excellent reactivity, generality (processed by the major PARG enzymes), stability, and usability. A second substrate, TFMU-IDPr, selectively reports on PARG activity only from the enzyme ARH3. Use of these probes in whole-cell lysate experiments has revealed a mechanism by which ARH3 is inhibited by cholera toxin. TFMU-ADPr and TFMU-IDPr are versatile tools for assessing small-molecule inhibitors in vitro and probing the regulation of ADP-ribosyl catabolic enzymes. Graphical Abstract: Highlights: Synthesis of fluorescent substrates that are enzymatically cleaved by PARG and ARH3 Synthesis of a fluorescent substrate that is enzymatically cleaved by ARH3 only Use of these substrates in cell lysate to measure PARG and ARH3 activity Discovery that ARH3 is inhibited by the metabolite ADP-ribosyl arginine Abstract : Drown et al. describe the design and synthesis of fluorescent activity probes for the (ADP-ribosyl)hydrolases PARG and ARH3. These probes are operational in biochemical assays or in cell lysate, and were utilized to identify an endogenous inhibitor of ARH3.